Detection of Pyuria versus Bacteriuria in Suspected Patients of Urinary Tract Infection - Dongol, Anjila; Joshi, Durga Man; Gautam, Avishekh (Nepal Journal of Science and Technology, 2015)
Urinary tract infection (UTI) is one of the most important causes of mortality and morbidity in the world affecting all age groups across the life span. The aim of this study is to determine incidence of bacteriuria and its relation with pyuria in suspected urinary tract infection. This crosssectional-descriptive-analytical study was conducted in microbiology section of Kathmandu Hospital, Tripureshwor from May to August 2011. During this period, 412 midstream urine samples collected were investigated by microscopic examination of centrifuged urine sediment and conventional semi-quantitative culture technique. Out of 412 MSU samples, 120 (29.13%) were culture positive. The remaining 22 (18.33%) samples showed low count significant bacteriuria (i.e 104-105 CFU/ml) and 98(81.67%) showed significant bacteriuria (i.e. ≥ 105 CFU/ml). Among 88 urine samples with significant pyuria, only 74 (84.09%) showed culture positive. Out of 324 urine samples without significant pyuria, 46 (14.19%) urine samples showed culture positive result. Significant pyuria was found to have sensitivity of 61.67%, specificity of 95.21% and the test has 84.09% positive predictive value in detecting bacteriuria. Pyuria and bacteriuria may not always correlate in the suspected case of UTI. DOI: http://dx.doi.org/10.3126/njst.v15i1.12029 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 129-132